2020
DOI: 10.1142/s0219581x19500054
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Seed Layer on Surface Morphology of ZnO Thin Films Grown by SILAR Method

Abstract: Zinc oxide (ZnO) nanostructured seed layer was grown by successive ionic layer adsorption and reaction (SILAR) method on glass substrate. The as-prepared nanostructured seed layer was characterized by X-ray diffraction (XRD) and scanning electron microscope (SEM) for its structure and surface morphology. XRD results showed a ZnO seed layer growth oriented along the (100) direction. Study of surface morphology showed ZnO nanocrystal clusters with hexagonal shape. ZnO nanorods (NRs) have been grown over the as-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…In figure 3(b1) and (b2), the distribution of flower-like structures of ZnO products is shown to be restricted for a film thickness of ≈150 nm. Increasing the film thickness to 330 nm results in the growth of perfect hexagonal shaped nanorods as shown in figure 2(c1) and (c2) [63].This demonstrates the feasibility of generating an aligned array of ZnO nanorods through an in situ deposition method that is comparable to the commonly employed intricate techniques [64]. The effect of film thickness on the surface morphology of nanostructured ZnO thin films has been investigated in several studies.…”
Section: Morphological Propertiesmentioning
confidence: 72%
See 1 more Smart Citation
“…In figure 3(b1) and (b2), the distribution of flower-like structures of ZnO products is shown to be restricted for a film thickness of ≈150 nm. Increasing the film thickness to 330 nm results in the growth of perfect hexagonal shaped nanorods as shown in figure 2(c1) and (c2) [63].This demonstrates the feasibility of generating an aligned array of ZnO nanorods through an in situ deposition method that is comparable to the commonly employed intricate techniques [64]. The effect of film thickness on the surface morphology of nanostructured ZnO thin films has been investigated in several studies.…”
Section: Morphological Propertiesmentioning
confidence: 72%
“…Another study by Carra et al [66] demonstrated that the deposition parameters could be adjusted to obtain ZnO films with various morphologies, such as columnar structures. Ali et al [64] investigated the effect of cobalt doping on the surface morphologies of ZnO thin films and discovered that the grain size, crystal population, morphology, film thickness, and crystallinity varied with different dopant concentrations.…”
Section: Morphological Propertiesmentioning
confidence: 99%